Mysterian Social Trinitarianism: Responding to Charges of Projection, Anthropomorphism, and Apophasis - Bray, Dennis (Verbum Vitae, 2023)
The landscape of current trinitarian theology seems to be settling into three chief domains: Latin (or classical) trinitarianism, social trinitarianism, and apophatic (or mysterian) trinitarianism. In this article I look at three main objections to social trinitarianism. The first objection, voiced most forcefully by Karen Kilby, is that the social view follows a vicious pattern of projection. The second objection, related to the first, is raised on grounds of anthropomorphism. According to this objection, social trinitarians employ the notion of mutual love, a notion which raises big concerns among cotemporary Thomists. The third objection is grounded in the inability of humans to know much about the divine being, or for our language to make true statements about God. If we do not know about God’s essence, then social trinitarians do not know most (or all) of what they claim to know. This line of thinking is very recently proposed by Katherine Sonderegger. I detail the main contours of each of the three objections and argue that none of them are strong enough to warrant the rejection of social trinitarianism. However, if apophaticism ultimately forces trinitarians to reject the social theory, there is still some room for a mysterian social trinitarianism. I outline the contours of such a view and explain its motivations and limits.